10. - (a - x) - (5.1 + x) + a -5,1
11. (b - x) - (a - x) + (a - b)
12 - (a + 3,3) - (x - a) -3,3 + x
13 (2.43 + 11) - (b + 2.43) + (6 - 1,1)
14. (1.53 - x + a) - (x - 1,53 - a)- a
15 - (a - 1.21) - (1 - a) - (0,21 - a)
быстрей

hessous hessous    2   18.09.2019 14:51    1

Ответы
адильнури адильнури  08.10.2020 00:15

Объяснение:

- (a - x) - (5.1 + x) + a -5,1=

=- a +x - 5.1 - x + a -5,1=-10,2

(b - x) - (a - x) + (a - b)=

= b - x - a + x+ a - b=0

- (a + 3,3) - (x - a) -3,3 + x=

= - a - 3,3- x + a -3,3 + x=-6,6

(2.43 + 11) - (b + 2.43) + (6 - 1,1)=

=2.43 + 11 - b -2.43 + 6 - 1,1=9,9-b

(1.53 - x + a) - (x - 1,53 - a)- a=

= 1.53 - x + a- x +1,53 + a- a=3,06

- (a - 1.21) - (1 - a) - (0,21 - a)=

=- a +1.21 - 1 +a- 0,21 +a=a

ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Алгебра